Perspectives for present and future CDMA-based communications systems. - Fantacci, Romano (IEEE Communications magazine)
In this article the main boosters of future CDMA communication systems are presented and described in order to highlight the ways to cope with the more challenging requirements of future systems and services. Particular attention is devoted to the inherent weak points of CDMA systems and detection techniques that can be used to overcome their impairments. Moreover, high-data-rate transmissions in wireless channels require proper link adaptation techniques; these are thoroughly described as well. Finally, the last part of this article focuses on the design of suitable protocol strategies for new heterogeneous multimedia packet services characterized by strict QoS requirements.